Media ethics in Asia : addressing the dilemmas in the information age - Iyer, Venkat; Asian Media Information and Communication Centre; Nanyang Technological University. School of Communication and Information (Singapore : Asian Media Information and Communication Centre and the School of Communication and Information, Nanyang Technological University, 2002)
This book addresses the range of debate and perspectives on issues of media ethics in the region, from the problems faced by journalists to public credibility of media institutions. Whilst debate in these areas is not new, with the rapidly changing media scene it has certainly gained in intensity.
The book grew out of a seminar of the same name organized by AMIC and supported by the Swedish International Development Cooperation Agency (Sida) in Kuala Lumpur in 2000.
Includes index.
Keywords: Sociology -- Asia. -- Mass media; Mass media -- Moral and ethical aspects -- Asia